KEMAMPUAN AKRUAL DAN ARUS KAS MEMPREDIKSI HARGA SAHAM MELALUI PERSISTENSI LABA - Muhammad Wahyuddin Abdullah (EKUITAS (Jurnal Ekonomi dan Keuangan), 2011)
The objective of research seems to examine the effect of accrual and cash flow components in predicting earnings persistence. Research also aims at observing the effect of earnings persistence on stock prices, understanding the effect of accrual and cash flow components in predicting stock prices through earnings persistence. Hypotheses test considers contextual model and path analysis to connect the models in manner of causality. Research population includes manufacturing companies listed at Indonesia Stock Exchange in the financial reporting period 1999-2007. Judgment sampling criteria has been used to produce 51 companies with 5 observations for each company, resulting in data pooling of 255 companies. Empirical two model examination produces the probability of significant effect on endogenous variable, which is earnings persistence and stock prices. Individually, accrual and cash flow components have significant effect in predicting earnings persistence, earnings persistence as sustainable earnings prospect have shown significant effect on stock prices. The examination against accrual component ability in predicting stock prices indicates the coefficient of earnings persistence path as a significant mediator. The observation against cash flow component ability in predicting stock prices, however, does not show the coefficient of earnings persistence path as the significant mediator.